2003
DOI: 10.1081/ese-120024449
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic Effect of Broad-Band Electromagnetic Field on Neonatal Mice (Mus musculus)

Abstract: Pregnant mice (Mus musculus), strain Swiss Webster, were exposed to a continuous electromagnetic field (12.8V/m) beginning in the third week of pregnancy. Histological and hematological analysis showed gender specific responses in 21 day-old mice after in-utero and post-natal continuous exposure. Automated lymphocyte percentage and total white blood cell counts were significantly elevated in exposed 21 day-old female mice compared to control mice. Lymphoma-like cells were seen in higher numbers in exposed 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…A higher observation of mild hepatic chronic inflammatory population, without other associated changes, indicated a slight influence of ELF-EMF on offspring pathologies. Similar results were also observed in literature [21], who reported that the pathological changes observed in 21-day-old mice that were exposed to fields of different intensities and frequencies were not specific to EMF exposure. In the present study, the only statistically significant observations in the dams were myocardial hypertrophy in the exposed and splenic erythrocatheresis in the control ones.…”
Section: Histological Findingssupporting
confidence: 80%
“…A higher observation of mild hepatic chronic inflammatory population, without other associated changes, indicated a slight influence of ELF-EMF on offspring pathologies. Similar results were also observed in literature [21], who reported that the pathological changes observed in 21-day-old mice that were exposed to fields of different intensities and frequencies were not specific to EMF exposure. In the present study, the only statistically significant observations in the dams were myocardial hypertrophy in the exposed and splenic erythrocatheresis in the control ones.…”
Section: Histological Findingssupporting
confidence: 80%
“…A progressive increase in lymphocyte percentage was observed in the mice in both station 1 and 2 after 90 days (81.4% and 87.6% Vs 74%; p<0.05), tending towards an absolute lymphocytosis. This finding was corroborated by Gagnon et al (2003), on teratogenic effect of broadband electromagnetic field on neonatal mice (Mus musculus). Increase in the values of haematological parameters investigated in this study; strongly indicate an increase in haemopoetic process, possibly induced by electromagnetic effects on mice bone marrow stem cell proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 70%
“…This occurs partly through the influence of Treg cells on neutrophil survival, as evidenced by a significantly enhanced nuclear hypersegmentation in neutrophils recovered from mice with reduced Treg‐cell numbers. Nuclear hypersegmentation is strongly associated with non‐infectious inflammatory conditions 19–21 and is historically associated with older neutrophils and prolonged survival. More recently, hypersegmented neutrophils resulting from granulocyte colony‐stimulating factor treatment, 22 exhibited increased survival and increased phagocytic and cytolytic capacity 23,24 .…”
Section: Discussionmentioning
confidence: 99%